1993
DOI: 10.1089/end.1993.7.457
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Renal Morphology and Vascular Function by Color Flow Doppler Sonography Immediately after Extracorporeal Shock Wave Lithotripsy

Abstract: Thirteen male and seven female patients with renal calculi were evaluated by color flow Doppler sonography (CFDS) for renal morphology and function before and after receiving 1000 to 2350 shocks with the Dornier MPL 9000 lithotripter. No significant morphologic change was encountered except for renal enlargement thought to be secondary to edema induced by shock wave application. Similarly, no significant differences were recorded in the systolic and diastolic flow rates or pulsatility (PI) or resistive (RI) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 12 publications
3
12
0
Order By: Relevance
“…Currently, an increase in RI values is expected after SWL therapy, which has been confirmed in many studies, though there are a few exceptions [11,18]. In the present study, we found higher RI values after SWL sessions in patients in both groups, comparable to that reported previously in literature.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Currently, an increase in RI values is expected after SWL therapy, which has been confirmed in many studies, though there are a few exceptions [11,18]. In the present study, we found higher RI values after SWL sessions in patients in both groups, comparable to that reported previously in literature.…”
Section: Discussionsupporting
confidence: 91%
“…Although some authors showed no change in kidney RI, most studies reported increased RI values after SWL sessions [18][19][20]. The discrepancies between studies might be due to study group differences and study population heterogeneity.…”
Section: Discussionmentioning
confidence: 95%
“…They evaluated RI in 20 patients 24 h after ESWL. 22 Kataoka et al reported that significant increases in RI were observed in 23 patients immediately after treatment with the Dornier MPL 9000 lithotriptor. 23 In another study Knapp et al reported a positive linear correlation between patient age and post‐ESWL changes in RI.…”
Section: Discussionmentioning
confidence: 99%
“…The RI is the parameter that has been most widely studied, [9][10][11][12][13][22][23][24]26 however, its pattern of response to acute renal tissue damage after ESWL has not been well defined. By comparison, there is general agreement that in the case of acute urinary obstruction, a few hours most likely would not be sufficient to allow the RI to reach pathologic values in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed the same alterations in RI values. Bedük et al assessed 24 patients before and 24 hours after ESWL. They found no significant change in RI values.…”
Section: Discussionmentioning
confidence: 99%